Retrospective analysis of indications of primary caesarean sections done at a tertiary care hospital - Datta, Kamna; Singh, P.; Chopra, Namita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section rates have globally risen above the levels that can be considered medically necessary. The aim of the study is to analyze the rate and indications of caesarean sections for primigravidae in the period 2016 to 2018 at a tertiary care hospital in Delhi. Methods: It is a retrospective observational study conducted in the Department of Obstetrics and Gynaecology at PGIMER and Dr RML Hospital, New Delhi. A total of 552 caesarean deliveries in primigravidae were studied. Results: The total deliveries during the study period were 3346 and the total caesarean section rate observed was 30.66%. The caesarean section rate among primigravidae was 29.1%. The rate of caesarean section in primigravidae rose from 22.7% in 2016 to 39.3% in 2018 with 17% increase. Majority of them belonged to the age group 20-30 years (79.34%) and 2.53% were elderly primigravidae. Out of the total number of primigravidae caesarean deliveries, 67.2% were performed in emergency and 32.7% were performed electively. Among the emergency caesarean sections performed, 64% of patients had induced labor and 22% had spontaneous labor. The most common indication of caesarean section was fetal distress (19.77%) followed by arrest of labor (17.87%) and malpresentations (8.9%). The short-term caesarean morbidity rate was 25.4% including one mortality. Wound infection was the most common complication. Conclusions: Various reasons like changing maternal risk profile increased IVF pregnancies, scientific advances, personal choice and medico legal considerations have been cited for increased caesarean rate. Following evidence-based labor protocols, judicious use of cardiotocography, proper patient selection for labor induction and patient education will contribute in reduction of caesarean sections and related complications.